Clinical equivalence of amlodipine medications in arterial hypertension patients - L. I. Markova; A. E. Radzevich; G. D. Morgun (Российский кардиологический журнал)
The study was focused on clinical equivalence of two amlodipine medications (cardilopin and norvasc) in patients with Stage I-III arterial hypertension (AH). Forty-two patients (mean age 52.1±3.9years) were divided into two groups, according to cardilopin or norvasc administration. At baseline and 6 months later, echocardiography (EchoCG), Doppler cardiac and vessel sonography were performed. Monthly blood pressure (BP) control demonstrated that BP target level was achieved by the end of Month One and sustained till the study's end, at similar doses of norvasc and cardilopin (5-10 mg/d). By the end of the study, left ventricular (LV) myocardial mass reduced, and prevalence of normal LV geometry increased, with significant improvement in LV diastolic function in both groups. Initially decreased linear blood flow parameters and pulse index, as well as increased extracranial vascular resistance, normalized by 6 months. Hemodynamic parameters were similar in both groups. According to its beneficial influence on initially disturbed hemodynamics, LV geometry and cerebral blood flow in AH patients, cardilopin is as effective as norvasc.